Evaluation of Nutritional Composition and Lead Detection in Suckermouth Catfish (Pterygoplichthys sp.) Egg Flour as a Candidate Feed Additive for Fish Feed - Masriah, Andi; Dwi Cahya, Muhamad; Islamy, R Adharyan; Nur Nadiro, Vina; Maulidiyah, Vika; Supriyadi, Supriyadi; Ramadhan, Adam Ashil; Hardiyanto, Revanina Putri (Hasanuddin University, 2025)
This study aims to evaluate the nutritional value and heavy metal lead (Pb) content in suckermouth catfish (Pterygoplichthys sp.) egg meal as a candidate feed additive in fish feed. The fish eggs were obtained from fishermen's catches in public waters in East Java, then cleaned, dried, and processed into meal for analysis. The proximate parameters tested included protein, fat, crude fiber, and ash content using the AOAC standard method, while Pb content was analyzed using Atomic Absorption Spectrophotometry (AAS). The results showed that suckermouth catfish egg meal had the following nutritional composition: protein 39.25±0.02%, fat 9.19±0.01%, crude fiber 2.36±0.03%, and ash 4.95±0.02%. This nutritional profile indicates that suckermouth catfish eggs are a high source of animal protein and have a low fiber content, thus having the potential to improve feed quality through the addition of essential amino acids and energy. Heavy metal Pb content was not detected within the sensitivity limits of the instrument, thus this product meets the safety aspects of feed ingredients related to heavy metal contamination. Overall, the results of this study indicate that suckermouth catfish egg meal has competitive nutritional value compared to several conventional feed ingredients and is safe from Pb contamination. Thus, this ingredient has the potential to be developed as an alternative feed additive in fish feed formulations.